PELAKSANAAN PENCATATAN PERKAWINAN OLEH PASANGAN TIONGHOA YANG AGAMA BUDDHA PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL DI KECAMATAN PONTIANAK UTARA KELURAHAN SIANTAN HULU - NIM. A1012191001, ANTHONY ASTRAWINATA (Fakultas Hukum Universitas Tanjungpura, 2022)
AbstracMarriage is an inner and outer bond between a man and a woman based on love (Metta), affection (Karuna), and a sense of responsibility (Mudita) with the aim of forming a happy family. In the marriages of Buddhist Chinese couples who got married at the Vihara, the marriages were carried out only according to religion. The consequences of this for Chinese couples who lacked knowledge did not register their marriages at the Population and Civil Registry Service Office.From the results of the background of the problem above, the author found the formulation of the problem whether a Chinese couple in North Pontianak District, Siantan Hulu Village who had their marriage based on Buddhism done at the Mulia Dharma Vihara had registered their marriage at the Pontianak City Population and Civil Registry Office. In this study the research objectives were to obtain data and information regarding marriage registration, to reveal the factors causing Chinese couples not to register, to reveal the legal consequences of marriages not being registered, and to reveal legal remedies for Chinese couples who did not register. In preparing the thesis the author uses empirical research methods, in the nature of field research and literature.Based on the results of the research conducted, that the marriage of Chinese couples in North Pontianak District, Siantan Hulu Village, in terms of marriage according to their religion, several couples have not registered at the Office of the Population and Civil Registry Office, due to factors that cause weak legal awareness, difficult registration procedures, and do not want to deal with government agencies. The consequence of unregistered marriages is that they do not have legal evidence, and the status of the children is unclear. To overcome this problem, the efforts that can be made by the Office of the Population and Civil Registry Service provide education or legal counseling on a regular basis through electronic media the importance of registering marriages for couples who are about to marry, and collaborating with Buddhist leaders around providing guidance on marriage. to a Chinese couple in North Pontianak District, Siantan Hulu Village who will have a marriage at the monastery regarding the Marriage Certificate.Keyword : Chinese Couple, Marriage, Registration, Legitimacy, and Chinese Couple Abstrak Perkawinan adalah ikatan lahir batin antara pria dan wanita yang berlandaskan cinta kasih (Metta), kasih sayang (Karuna), dan rasa sepenanggungan (Mudita) dengan tujuan untuk membentuk keluarga yang bahagia. Dalam perkawinan Pasangan Tionghoa beragama Buddha yang melangsungkan perkawinan di Vihara, perkawinan yang dilakukan hanya menurut agama konsekuensi dari hal tersebut bagi Pasangan Tionghoa yang minim pengetahuan tidak mencatatkan perkawinannya pada Kantor Dinas Kependudukan dan Catatan Sipil. Dari hasil latar belakang masalah diatas penulis menemukan rumusan masalah apakah Pasangan Tionghoa di Kecamatan Pontianak Utara Kelurahan Siantan Hulu yang melakukan Perkawinannya Berdasarkan Agama Buddha Dilakukan di Vihara Mulia Dharma telah mencatatkan perkawinannya di Kantor Dinas Kependudukan dan Catatan Sipil Kota Pontianak. Dipenelitian ini Tujuan Penelitian untuk mendapatkan data dan informasi mengenai pencatatan perkawinan, Mengungkapkan faktor penyebab Pasangan Tionghoa tidak mencatatkan, Mengungkapkan akibat hukum Perkawinan tidak dicatatkan, dan mengungkapkan upaya hukum bagi Pasangan Tionghoa yang tidak mencatatkan. Dalam penyusunan skripsi penulis menggunakan metode penelitian empiris, dalam sifat penelitian lapangan dan kepustakaan. Berdasarkan hasil penelitian yang dilakukan, bahwa perkawinan Pasangan Tionghoa di Kecamatan Pontianak Utara Kelurahan Siantan hulu, dalam hal perkawinan menurut agamanya beberapa pasangan belum melakukan pencatatan di Kantor Dinas Kependudukan dan Catatan Sipil, karena faktor yang menyebabkan lemahnya kesadaran hukum, prosedur mencatatkan yang sulit, dan tidak mau berurusan dengan instansi pemerintahan. Akibat dari perkawinan yang tidak dicatatkan adalah tidak memiliki bukti sah, serta status anak yang tidak jelas. Untuk mengatasi masalah ini, maka upaya yang dapat dilakukan oleh pihak Kantor Dinas Kependudukan dan Catatan Sipil memberikan edukasi atau penyuluhan hukum secara rutin melalui media elektronik pentingnya mencatatkan perkawinan bagi pasangan yang akan menikah, dan melakukan kerjasama dengan pihak Pemuka Agama Buddha disekitar memberikan pembinaan mengenai perkawinan kepada Pasangan Tionghoa di Kecamatan Pontianak Utara Kelurahan Siantan Hulu yang akan melangsungkan Perkawinan di Vihara mengenai Akta Perkawinan.Keyword : Pasangan Tionghoa, Perkawinan, Pencatatan, Keabsahan, dan Pasangan Tionghoa